Antibiotic resistance in urinary tract infection in children - Goroftei, Larisa; Matache, Elena-Roxana; Răileanu, Cosmin Răducu; Peptine, Lucian; Ilie, Lăcrămioara; Mihalache, Tiberiu; Grigore, Ionica; Lisă, Lăcrămiora Elena; Nechita, Aurel; Gurău, Gabriela; et al. (Technium BioChemMed, 2022)
This retrospective study (November 2021-October 2022) aimed at identifying pathogen agents from positive urine cultures and tested their resistance to antibiotics at Emergency Clinical Hospital for Children “Sf. Ioan” in Galati, Romania. Included in this study were 167 bacterial strains and both Gram-positive and Gram-negative bacteria have been isolated. Most bacterial strains were Escherichia coli(56,28 %), Klebsiella pneumonia (12,57 %), Proteus mirabilis(8,38 %) and Enterococcus faecium (12,57 %). Others bacterial strains were: Pseudomonas aeruginosa (4,79 %), Staphylococcus saprophyticus (1,20 %), Staphylococcus epidermidis (0,59 %), Staphylococcus schleiferi (0,59 %), Staphylococcus aureus MSSA (0,59 %), Staphylococcus aureus MRSA (0,59 %), Streptococcus agalactiae (0,59 %), Enterobacter cloacae (0,59 %), Acinetobacter baumanii (0,59 %). Escherichia coli was the most frequent etiologic pathogen, being responsible for half of urinary tract infection (UTI) and the highest resistance in terms of pathogens was found among this bacteria. This research found a high rate of resistance to ampicilin and followed by co-trimoxazole, cephalosporines and aminoglycosides. Antimicrobial resistance in urinary tract infection in our days is a real threat that requires vigilant monitoring to be done.